2020
DOI: 10.1021/acsnano.0c07722
|View full text |Cite
|
Sign up to set email alerts
|

All-Dielectric Metasurface Fluorescence Biosensors for High-Sensitivity Antibody/Antigen Detection

Abstract: Protein biomolecules are used as markers for various diseases and infections and are targets in biosensing research and development. One of the highest-sensitivity biosensing techniques is considered to be fluorescence (FL) sensing. However, to our knowledge, no study has shown that all-dielectric metasurfaces can contribute to highly sensitive FL sensing. Here, we introduce an efficient type of FL-sensing platforms and show that all-dielectric metasurface FL biosensors are able to directly detect a representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 38 publications
0
59
0
Order By: Relevance
“…[143,144] All-dielectric metasurfaces have also been applied for bio molecular detection using enhanced fluorescence. [142] For example, Iwanaga et al demonstrated the detection of antibodies and antigens with high sensitivity and improved detection limit using an all-dielectric silicon metasurface together with a sandwich assay protocol. [142] They found that the electric field intensity has a maximum at the outermost surface of the resonators (Figure 2l), leading to highly enhanced fluorescence.…”
Section: Surface-enhanced Fluorescence Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…[143,144] All-dielectric metasurfaces have also been applied for bio molecular detection using enhanced fluorescence. [142] For example, Iwanaga et al demonstrated the detection of antibodies and antigens with high sensitivity and improved detection limit using an all-dielectric silicon metasurface together with a sandwich assay protocol. [142] They found that the electric field intensity has a maximum at the outermost surface of the resonators (Figure 2l), leading to highly enhanced fluorescence.…”
Section: Surface-enhanced Fluorescence Sensingmentioning
confidence: 99%
“…[142] For example, Iwanaga et al demonstrated the detection of antibodies and antigens with high sensitivity and improved detection limit using an all-dielectric silicon metasurface together with a sandwich assay protocol. [142] They found that the electric field intensity has a maximum at the outermost surface of the resonators (Figure 2l), leading to highly enhanced fluorescence. In addition, carcinoembryonic antigen (CEA) detection was successfully performed well below the clinical diagnostic level of 5 ng mL −1 and reached a detection limit of 0.85 pg mL −1 (Figure 2k).…”
Section: Surface-enhanced Fluorescence Sensingmentioning
confidence: 99%
“…Analogous to their metallic counterparts, as mentioned earlier, dielectric metastructures provide strong sensitivity to the perturbations in the permittivity of the surrounding media along with robust magnetic-field localization. [80,108,112,114,115,117] Among different types of dielectric materials, low-loss behavior and CMOS compatibility of silicon have triggered researchers to develop all-dielectric metastructures for diverse purposes from transducing to biological sensing [355][356][357][358] and imaging. [100,358,359] Within this concept, recently, Quidant's group developed all-dielectric silicon-based nanophotonic metasensors for the detection of prostate-specific antigen (PSA) in human serum and mechanistically unveiled the role of magnetic and electric dipoles in boosting the sensing performance of the device.…”
Section: Magnetic Metasensorsmentioning
confidence: 99%
“…[106,107] From the biosensing perspective, metasurfaces have revitalized ultraprecise and sensitive label-free biomarker detection techniques with the remarkable figure of merit (FOM) and sensitivity values for point of care (POC) applications, due to 1) robust electromagnetic field confinement at subwavelength scales and 2) high Q/V e ratio. [16,24,78,81,[106][107][108][109][110][111][112][113][114][115] Furthermore, metasurfaces provide a large active region, which satisfies the diagnosis and quantification of the interactions between resonating unit cells and biological entities. [80,[115][116][117][118][119] Exploiting these advantages, several ultrasensitive and precise metasensors have been designed and extended towards probing of virus carriers, such as Zika virus envelope protein, [120][121][122] SARS-CoV-2 spike protein, [123,124] HIV-1 subtypes (A, B, C, D, E, and BC), [124,125] and many other analogous biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, label-free plasmonic biosensing has attracted more attention, which is feasible on the development of environmentally-friendly portable instruments and demonstrates the potential for point-of-care testing. Compared with the biosensing performance of the important dielectric metasurface counterpart [ 39 , 40 ], plasmonic metasurface has a lower quality (Q) factor of resonance, but their biomolecule sensitivity is usually much higher. This is attributed to the greater near-field concentration and confinement, which is typically within the size scope various biomolecules [ 10 ].…”
Section: Introductionmentioning
confidence: 99%